Ø¹Ù„ÙŠ Ù‡Ø§Ø´Ù…ÙŠ Ù‡Ùˆ Ø²Ø¹ÙŠÙ… Ø§Ù„Ø§ØµÙ„Ø§Ø ÙÙ‰ Ù…Ø¬Ø§Ù„ Ø§Ù„ØªØ±Ø¨ÙŠØ© Ø¨Ø¢ØªØ´ÙŠÙ‡ - Gade, Syabuddin (SCAD Independent, 2014)
This papers the application of the historical method and descriptive and analytical -Looking for Ali Hasjmy, a famous man and a leader of the reform in the field of education in the 20th century in Aceh. And not only has a lot of educational views, established on some of the books, but also it contributes to the task in building the field of education and repaired and developed since his Aceh governor in the years 1957-1964. And was a contribution written in the history of the city of students of Darussalam, especially in the development of the Syiah Kuala University, State Islamic University of Ar-Raniry, Institute of Tengku Chik Pante Kulu, APDN (Academy of the Government of the Interior), and build a ?village students? (Kampung pelajar) and